Migratory Zooplankton Excreta and Its Influence on Prokaryotic Communities - Maas, Amy E.; Liu, Shuting; Bolaños, Luis M.; Widner, Brittany; Parsons, Rachel; Kujawinski, Elizabeth B.; Blanco-Bercial, Leocadio; Carlson, Craig A. (Frontiers in Marine Science, 2020)
Particulate organic matter (fecal pellets) from zooplankton has been demonstrated to be important nutrient sources for the pelagic prokaryotic community. Significantly less is known about the chemical composition of the dissolved organic matter (DOM) produced by these eukaryotes and its influence on pelagic ecosystem structure. Zooplankton migrators, which daily transport surface-derived compounds to depth, may act as important vectors of limiting nutrients for mesopelagic microbial communities. In this role, zooplankton may increase the DOM remineralization rate by heterotrophic prokaryotes through the creation of nutrient rich “hot spots” that could potentially increase niche diversity. To explore these interactions, we collected the migratory copepod Pleuromamma xiphias from the northwestern Sargasso Sea and sampled its excreta after 12-16 h of incubation. We measured bulk dissolved organic carbon, dissolved free amino acids via high performance liquid chromatography and dissolved targeted metabolites via quantitative mass spectrometry (UPLC-ESI-MSMS) to quantify organic zooplankton excreta production and characterize its composition. We observed production of labile DOM, including amino acids, vitamins and nucleosides. Additionally, we harvested a portion of the excreta and subsequently used it as the growth medium for mesopelagic (200m) bacterioplankton dilution cultures. In zooplankton excreta treatments we observed a four-fold increase in bacterioplankton cell densities that reached stationary growth phase after five days of dark incubation. Analyses of 16S rDNA amplicons suggested a shift from oligotrophs typical of open ocean and mesopelagic prokaryotic communities to more copiotrophic bacterial lineages in the presence of zooplankton excreta. These results support the hypothesis that zooplankton and prokaryotes are engaged in complex and indirect ecological interactions, broadening our understanding of the microbial loop.